Caracterização epidemiológica e avaliação de risco associada a presença de ectoparasitos em granjas de postura comercial em Minas Gerais - Tiago Mendonca de Oliveira (2017)
In recent years the Brazilian poultry has undergone a scientific and technological evolution that has resulted in high density of laying hen farms buildings and in the increase of the occurrence of ectoparasites such as flies, lice and mites. The presence of those ectoparasites has been causing negative impacts for the aviculture, once, these can be responsible for the stress increase and appearance of diseases and, besides, reduction in the productivity. The objective of this work was to identify and to characterize the risk for the presence of hematophagous mites, Megninia spp., lice and flies associating to the factors related to the environment of the poultry houses of laying farms in the state of Minas Gerais. An observational and descriptive study was carried out using a secondary database with information about the presence and absence of ectoparasites, characteristics of poultry houses, poultry, facilities, geographic location and management. In order to evaluate the intensity of poultry houses with the presence of ectoparasites a spatial analysis was carried out through the construction of kernel maps. A risk index was built for each ectoparasite group in order to evaluate the risk for the presence of those parasites using for that the Correspondence Analysis. A high frequency of hematophagous mites (48%) was observed, of Megninia spp. (19,40%), of lice (21%) and of flies (62,93%) poultry houses of the farms in the state of Minas Gerais. It was verified by the Correspondence Analysis that the risk index for the group of hematophagous mites was associated to the interval of removal of manure. For the group of Megninia spp. there was an association between the risk index and the age of the poultry. Already for the Phthiraptera order, an association was observed between the risk index and the presence of synanthropic birds, as pigeons (Columbia livia), guira and ani cuckoo birds (Guira guira, Crotophaga ani), the presence of subsistence chickens in the adjacencies of the poultry houses and the use of fire broom (flame thrower) in the cages of the poultry farms. For the Diptera order, an association was verified between the risk index and the removal interval and humidity of the dejections, with the presence of ectoparasites in the shelter and with the installation type. The spatial analysis of the poultry establishments demonstrated that the ectoparasites are distributed in agreement with their biological, environmental, management and infrastructure of poultry houses characteristics. In addition, it is noticed by the analysis of the map the simultaneous presence of more than an ectoparasite group in the georeferenced counties. The results suggest that some management practices that consider the age of the poultry, the removal of dejections with larger periodicity, the contention of synanthropic birds and of subsistence chickens they could contribute in the decrease of the presence of hematophagous mites, of Megninia spp., of lice and of diptera in the poultry house of the farms.